2012
DOI: 10.1007/s11064-012-0902-2
|View full text |Cite
|
Sign up to set email alerts
|

Bacopa monnieri and l-Deprenyl Differentially Enhance the Activities of Antioxidant Enzymes and the Expression of Tyrosine Hydroxylase and Nerve Growth Factor via ERK 1/2 and NF-κB Pathways in the Spleen of Female Wistar Rats

Abstract: Aging is characterized by development of diseases and cancer due to loss of central and peripheral neuroendocrine-immune responses. Free radicals exert deleterious effects on neural-immune functions in the brain, heart, and lymphoid organs and thus, affecting the health. Bacopa monnieri (brahmi), an Ayurvedic herb, and L-deprenyl, a monoamine oxidase-B inhibitor, have been widely used in the treatment of neurodegenerative diseases. The purpose of this study was to investigate whether brahmi (10 and 40 mg/kg BW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
20
0
3
Order By: Relevance
“…Hence, our results are consistent with the notion that H2O2 plays a pivotal role in PKC activation via ROS generation. It has been shown that MAPK exists downstream of PKC and regulates many related transcription factors, including NF-κB and β-catenin, in several cell types, including human UCBMSCs and mouse ESCs (Yun et al, 2009;Yang et al, 2012;Lee do et al, 2013;Priyanka et al, 2013). We found that H2O2 was able to induce ERK and p38 MAPK activation, thereby stimulating NF-κB and β-catenin activation.…”
Section: Figurementioning
confidence: 52%
See 1 more Smart Citation
“…Hence, our results are consistent with the notion that H2O2 plays a pivotal role in PKC activation via ROS generation. It has been shown that MAPK exists downstream of PKC and regulates many related transcription factors, including NF-κB and β-catenin, in several cell types, including human UCBMSCs and mouse ESCs (Yun et al, 2009;Yang et al, 2012;Lee do et al, 2013;Priyanka et al, 2013). We found that H2O2 was able to induce ERK and p38 MAPK activation, thereby stimulating NF-κB and β-catenin activation.…”
Section: Figurementioning
confidence: 52%
“…In embryonic stem cells (ESCs), H2O2 is able to activate conventional, novel or atypical PKCs and so promote the activation of MAPKs ). In addition, it has been shown that phosphorylation of PKC and MAPK is required for the regulation of stem cell functions through the facilitation of multifunctional transcription factors, such as NF-κB and β-catenin Lee do et al, 2013;Priyanka et al, 2013). However, the coordination of signal transduction cascades downstream of H2O2 via effector molecules is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some studies have shown that EPA has the capability to directly and indirectly activate the nuclear factor kappa B (NF-κB) pathway (Kageyama et al 2013;Zuniga et al 2011), and this pathway is responsible for the control of the gene expression of several anti-oxidant enzymes, including CAT (Priyanka et al 2013). Thus, the modulation of NF-κB pathway by EPA may modulate the CAT content, and consequently, its activity, furthermore, allosteric mechanisms, can modulate the enzyme activity as demonstrated above.…”
Section: Discussionmentioning
confidence: 94%
“…Oil from seeds reported to contain up to 80% D-carvone which possess strong antioxidant potential against in vitro DPPH, ABTS, and FRAP tests. [73][74][75][76][77][78][79][80][81][82] Alcoholic extracts exhibited strong antioxidant potential against ferric sulfate, cumene hydroperoxide, and DPPH free radical scavenging tests in a dose-dependent manner . In a comparison of 1-deprnyl (antiaging, nootropic drug) and B. monnieri, it was found to enhance antioxidant/ detoxification enzyme activity in the spleen, brain, heart, thymus, and mesenteric lymph nodes thereby showing neuroprotection.…”
Section: -65]mentioning
confidence: 99%